PELATIHAN MODEL BEEF CONCEPT DISERTAI PUSH UP DAN JOGGING LEBIH MENINGKATKAN KETEPATAN SHOOTING FREETHROW BOLA BASKET DARI PADA PELATIHAN MODEL BEEF CONCEPT DISERTAI DUMBEL DAN JOGGING - Gangga Permana, I Kadek Arya; Astawa, Putu; Wihandani, Desak Made; Tirtayasa, Ketut; Jawi, I Made; Komang Satriyasa, Bagus (Sport and Fitness Journal; Volume 6, No.3, September 2018DO - 10.24843/spj.2018.v06.i03.p08, 2019)
ABSTRACT Introduction: The objective of a basketball game is to insert the ball into the opponent's basket and keep our basket alone so as not to concede the ball. This becomes important because it determines points to improve the ability and maximize points in the game so this needs to be trained. Free throw shots can be done using one hand or two hands. Whereas a free throw is a shot given to a player for committing an offense. This shot is done in the exact position behind the line of free shots in accordance with the rules. Purpose:This study aims to compare training model 1 (beef concept with push up and jogging) and training model 2 (beef concept with dumble and jogging) to improve the accuracy of free throw shooting. This research was conducted on 40 students of SMP Negeri 1 Kuta Selatan who were chosen in simple random which has fulfilled inclusion and exclusion criteria. The sample was divided into two groups so that each group was 20 people and given different treatment for six weeks. Group 1 was given model 1 training and Group 2 was given a model 2 training. Methods:The data obtained were analyzed by paired t- test to find the difference between before and after training in both groups and t-independent test to find the difference of shooting free throw accuracy between groups both before and after the training. The meaning limit is 0.05. The research design used is experimental design Randomized Pre and Post test Group Design. According to Pocock's (2008) theory, each group consisted of 20 groups of 1 and group 2. All groups were given preliminary tests, between treatment one and two treatment were given concurrent training, then each treatment was observed. Results:The result showed that the accuracy of free throw shooting between groups after training was 3.85 ± 1.09 in group 1 and in group 2 was 2.90 ± 1.12. The average accuracy of free throw shooting in training model 1 was higher than with model 2 training which was statistically significantly different with p = 0,010 (p <0,05). Conclution:From the results of this study it is concluded that the training of model 1 further improves the accuracy of free throw shooting rather than training model 2, Suggestion: in practice it is suggested to use training model 1 to improve the accuracy of free throw shooting. Keywords: beef concept, push up, jogging, dumble, free throw shooting